Field efficacy of acaricides against Varroa destructor. - María Jesús Gracia; Carlos Moreno; Montserrat Ferrer; Alfredo Sanz; Miguel Ángel Peribáñez; Rosa Estrada (PLoS ONE)
Field trials were conducted in Northeast Spain (Aragón) to evaluate the effectiveness of two acaricides against Varroa destructor. These experiments took into account the season of the year, apiary, colony, and developmental state and strength of the colony. The acaricides used were a synthetic (amitraz, Apivar®) and a natural (formulated from Api Life Var®, thymol oil and thymol alcohol) product. The treatments used in the present study reduce high infestations of V. destructor, although they do not eliminate the infestation. Similar efficacies between treatments were found. Nevertheless, the efficacy of a treatment depends on the apiary where applied. Moreover, the detected variability in the apiary and hive poses a challenge to the identification of the significant factors. Therefore, more field studies to assess efficacies in several apiaries are needed to obtain a better understanding of the effects of the applied treatments.